Semi-Empirical and HOMO, LUMO Studies of Some Chlorinated Pesticides Compounds (Communications in Computational Chemistry, 2025)
Theoretical studies on some chlorinated pesticides compounds namely:Heptachlor, Heptachlorepoxide and Chlordane as a first group, Aldrin and Endrin as asecond group, and DDT, Methoxychlor as a third group, were performed usingsemi-empirical quantum chemical calculation. Modified Neglect of Diatomic OverlapMNDO method was used to investigate the effect of positional variation of chlorine andoxygen atoms on the electronic and structure properties of the studied chlorinatedpesticides. The structure optimization of some electronic parameters such as heats offormation, total energies, electronic energy, binding energy, nuclear energy, ionizationenergies, electron affinities and dipole moment were calculated and discussed. Theenergy of the Highest Occupied Molecular Orbital (HOMO) and the energy of theLowest Unoccupied Molecular Orbital (LUMO) are also calculated. The LUMO-HOMO energy gap have been calculated and discussed. The stability and activity of thestudied compounds based on the obtained values have been investigated.